REVIVING KETOPRAK: THE ROLE OF THE YOGYAKARTA YOUTH SINEPRAK COMMUNITY IN CULTURAL PRESERVATION - Amanatillah, Dwi Nisa'; Jazuli, Muhammad; malarsih, Malarsih (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This research uses a case study approach to explore the role of the Sineprak community in preserving and developing the ketoprak performing arts in the modern era. The main focus of this research is on the intensive training process of actors and directors, which includes technical aspects and deepens the script and interprets the role. The COVID-19 pandemic forced Sineprak to switch to digital platforms, especially YouTube, which has attracted thousands of followers. However, after Bondan Nusantara's death, the frequency of performances decreased significantly. The community-based education process at Sineprak contains Javanese cultural values such as courtesy, etiquette and cooperation, which help shape the character of the younger generation. Innovations in the presentation of modern ketoprak, including combining elements of other performing arts and modern technology, have succeeded in attracting the interest of today's audiences. Documentation and publication via social media play an important role in expanding audience reach.